Predictive value of National Early Warning Score 2 (NEWS2) for intensive care unit admission in patients with SARS-CoV-2 infection. Issue 10 (2nd October 2020) - Gidari, Anna; De Socio, Giuseppe Vittorio; Sabbatini, Samuele; Francisci, Daniela
Abstract: Background : From January 2020, Coronavirus disease 19 (COVID-19) has rapidly spread all over the world. An early assessment of illness severity is important for the stratification of patients. We analysed the predictive value of National Early Warning Score 2 (NEWS2) for intensive care unit admission (ICU) in patients with Severe Acute Respiratory Syndrome- Coronavirus-2 (SARS-CoV-2) infection. Methods : Data of 71 patients with SARS-CoV-2 admitted from 1 March to 20 April 2020, to the Clinic of Infectious Diseases of Perugia Hospital, Italy, were retrospectively reviewed. NEWS2 at hospital admission, demographic, comorbidity and clinical data were collected. Univariate and multivariate analyses were performed to establish the correlation between each variable and ICU admission. Results: Among 68 patients included in the analysis, 27 were admitted to ICU. NEWS2 at hospital admission was a good predictor of ICU admission as shown by an area under the receiver-operating characteristic curve analysis of 0.90 (standard error 0.04; 95% confidence interval 0.82–0.97). In multivariate logistic regression analysis, NEWS2 was significantly related to ICU admission using thresholds of 5 and 7. No other clinical variables included in the model were significantly correlated with ICU admission. A NEWS2 threshold of 5 had higher sensitivity than a threshold of 7 (89% and 63%). Higher specificity, positive likelihood ratio and positive predictive value were found using a threshold of 7 than a threshold of 5. Conclusions : NEWS2 at hospital admission was a good predictor for ICU admission. Patients with severe COVID-19 were correctly and rapidly stratified.